Nonlinear Adjustment of ASEAN−5 Real Exchange Rates: Symmetrical or Asymmetrical? - Liew, Venus Khim-Sen (Economics Bulletin, 2004)
This study examines whether the nonlinear adjustment dynamic of exchange rate to the equilibrium level as documented in Liew et al. (2003, 2004) is symmetrical or asymmetrical. Following the sequential tests as proposed in Teräsvirta and Anderson (1993), this study is able to identify that the US dollar based real exchange rates of Indonesia, Philippines, Singapore and Thailand exhibit LSTAR−type nonlinearity, implying that the real exchange rates of these countries have asymmetrical responds towards appreciation and depreciation. This finding provides useful guidelines in the monitoring and stabilising of ASEAN exchange rates, in order to boost the economy of this region, which has experienced different extends of negative shocks in the past few years.